Design for Resilience: mitigation, adaptation and transformative design - Bilello, Joseph (ARCC Conference Repository, 2014)
From case studies of highly capitalized, architect-designed buildings confronted by natural and manmade disasters of the last decade, this paper extracts exemplary cases ofmitigation, adaption, transformation design (before, during, and after) disaster instances globally. Based on resilience attributes from biology and complexity theories (Zolli and Healy,2012), these cases, prepared with graduate students in courses on resilience and research methods, examine attributes that map onto architecture (i.e., simple cores/complex edges, modularity, etc.). Cases question how architects and designers can begin to address other resilience attributes that architecture does not (i.e. capacity for flocking/swarming). Disaster mitigation strategies of Ito and Suzuki in Sendai, Japan, adaptation design with shipping containers during 5000 earthquakes aftershocks period (2011-2012) in Christchurch, New Zealand, and transformative design strategies that changed the identity of Greensburg, Kansas via LEED designed buildings are cases abbreviated in the paper. Third, architects' roles before and after disasters have become well defined. In contrast, roles during disasters are absent from the literature and practice of architecture. Efforts to better ascertain critical roles for architects during relatively predictable disaster events (i.e. hurricanes, wildfire, storm surge, sea level rise, etc.) are next.